2014
DOI: 10.1080/21697213.2014.921366
|View full text |Cite
|
Sign up to set email alerts
|

Affiliated management and firm value: Evidence from China

Abstract: We provide evidence on how the presence of a top manager who is a controlling shareholder or the employee of a controlling shareholder (i.e. affiliated management) is associated with firm value. By analysing the data of Chinese listed firms in the A-share stock market from 2001 to 2009, we find that affiliated management is negatively associated with firm value. Furthermore, although firms with affiliated management have higher return on assets and return on sales, affiliated management is positively associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(53 reference statements)
0
1
0
1
Order By: Relevance
“…There are many ways to measure the company's value, including ROA, ROE, EPS, the sustainable growth rate, cumulative excess earnings CAR, and Tobin's Q [26][27][28][29][30][31][32][33][34], and there are many different ways to calculate Tobin's Q [29][30][31][32][33]. Table 1 shows the equation used in this paper.…”
Section: Firm Valuementioning
confidence: 99%
“…There are many ways to measure the company's value, including ROA, ROE, EPS, the sustainable growth rate, cumulative excess earnings CAR, and Tobin's Q [26][27][28][29][30][31][32][33][34], and there are many different ways to calculate Tobin's Q [29][30][31][32][33]. Table 1 shows the equation used in this paper.…”
Section: Firm Valuementioning
confidence: 99%
“…Especially in high-level financially developed regions, financing will be easier to be obtained in the market, thereby improving the level of vertical integration. Zheng et al. (2014) employed the ratio of the balance of deposits and loans in each province to Gross Domestic Production (GDP) as an indicator of the regional financial development level, and they also concluded that financial development can promote the adoption of integrated forms by enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai perusahaan dicerminkan sejumlah indikator, yaitu Price to Book Value (PBV) dan Tobin's Q. Jika kedua indikator ini meningkat artinya nilai perusahaan juga mengalami peningkatan. Khairiyani (2018), Zheng, Xue, & Chen (2014), dan Zhong & Zhang (2018) telah menggabungkan kedua indikator di atas untuk mengukur nilai perusahaan. Bursa Efek Indonesia mempunyai beberapa indeks.…”
unclassified